Interpretasi Kepemimpinan Perempuan dalam Pemikiran Kontemporer - Salsabila, Rayhanah; Sulthoni, Akhmad; Novitasari, Fajar (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
The role of women in puclic has always been a debate on the table topic, both among scholars and Muslim intellectuals, particularly in the terms of women leadership in. The reality that currently happening is undeniable that many of women qualified to be a leader and can perform their duties on an equal footing with men. The development of views and perspectives in society is capable to change the meaning of gender roles that were previously solely designated for males. This research aims to reinterpret leadership of women in contemporary thoughts. Similar to how other interpretations of verses, the pros and cons of women's leadership also supported by various sources of arguments and their evidences, one of them is surah An-Nisa' verse 34. In general, scholars firmly believe that the interpretation of this verse is a justification that only men are worthy of carrying out duties in the public. Referring to a number of tafseer literature, the definition qowwam is leader, person in charge, regulator, protector, and educator. This interpretation is strengthened by two reasons for the superiority of men over women. First, the ability to provide a living (wahbiyun) and, second, the ability to strive and work (kasbiyun).